Impact of number of helical fins mounted around a cylindrical tube inside a rectangular cavity installed under a solar panel - Alqaed, Saeed; Mustafa, Jawed; Sajadi, S. Mohammad; Aybar, Hikmet S. (Elsevier, 2024)
This article evaluates the effect of using nanofluids (NFs) flow in a thermal solar panel (SPL) numerically. A number of tubes are placed under the SPL, and phase change material (PCM) OM37 is utilized around the tubes. Laminar alumina/water NFs with a constant volume percentage of 2 % flows in the tubes. Helical fins are installed around the tubes. By changing the number of fins (NOFs) from 1 to 3, the average SPL temperature, maximum PCM temperature, outlet temperature of NFs, heat transfer coefficient (HTC), and PCM volume fraction are determined at the time range of from 0 to 1500 s. The NFs flow is modeled using a two-phase model and governing equations are solved utilizing the finite element method (FEM). The results demonstrate that the minimum amount of molten PCM occurs when the NOFs is 3 in the presence of NFs. The maximum amount of molten PCM occurs when the NOFs is 1 in the presence of water. The use of NFs flow in the tubes and three fins causes the average temperature in the SPL and the maximum temperature (TMX) in the PCM to be lower compared to other cases. The HTC is maximal when the NOFs is 3 in the presence of NFs. In this case, the value of the HTC is 3.4 % higher than the minimum HTC.
Keywords: Nanofluid; Helical fins; PCM; Solar energy